디지털 헬스케어 기기의 딥러닝 기반 SBOM 결함 탐지 기법 - 김희연 (The Graduate School, Ajou University, 2024)
This paper focuses on the digital innovation brought about by the advancement of ICT technology in the healthcare field. In particular, the introduction of cutting-edge technologies such as AI are contributing to the improvement of health care services, but at the same time, the risk of cybersecurity threats and software security problems in digital health care devices are emerging as well. Therefore, the importance of SBOM (Software Bill of Materials) to respond to such problems has now been emphasized, and this paper focuses on strengthening the cyber security of digital healthcare devices through the creation and application of SBOM. This study develops an AI-based software defect detection method and seeks to ensure the reliability and safety of digital healthcare devices by proposing an efficient method compared to existing rule-based approaches. This study aims to contribute to strengthening security by detecting flaws in digital healthcare devices through AI and establishing a technical foundation for providing ultimate quality healthcare services._x000D_ _x000D_ Keywords: SBOM, Deep Learning, Digital Healthcare Device, Software Defect Detection, Cyber security, Artificial Intelligence(AI)|본 논문은 ICT 기술의 발전이 보건의료 분야에 접목되면서 불러온 디지털 혁신에 주안점을 두고 있다. 특히 AI와 같은 최첨단 기술의 도입은 보건의료 서비스 향상에 기여하고 있으나, 이와 동시에 사이버보안의 위협과 디지털 헬 스케어 기기의 소프트웨어 보안 문제의 위험성이 대두되고 있다. 따라서 이와 같은 문제에 대응하기 위한 SBOM(Software Bill of Materials)의 중요성이 강 조하며, 본 논문은 SBOM 생성 및 적용을 통해 디지털 헬스케어 기기의 사이 버보안을 강화하는 데 중점을 두고 있다. 본 연구는 AI 기반의 소프트웨어 결 함 탐지 방법을 개발하여, 기존의 규칙 기반 접근법에 비해 효율적인 방법을 제안하여 디지털 헬스케어 기기의 신뢰성과 안전성을 보장하고자 한다. 본 연 구는 AI를 통해 디지털 헬스케어 기기의 결함을 탐지하여 보안성을 강화하고 궁극적인 양질의 보건의료 서비스를 제공할 수 있는 기술적 기반을 마련하는데 기여하고자 한다. _x000D_ _x000D_ 주제어: SBOM, 딥러닝, 디지털 헬스케어 기기, 소프트웨어 결함 탐지, 사이버보안, 인공지능(AI)
학위논문(석사)--지식정보공학과,2024. 2
Keywords: AI; SBOM; 디지털 헬스케어 기기; 딥러닝; 사이버보안; 소프트웨어 결함 탐지; 인공지능